The construction of English verb “send”: A cognitive linguistics study - Moch. Panji Prabaskoro; Prayudha Prayudha (Universitas Ahmad Dahlan)
This research is entitled “The Construction of English Verb “SEND”: A Cognitive Linguistic Study”. It is based on cognitive linguistic, because with cognitive linguistic it could be seen how exactly the construction of English verb “send” and how the construction could have that construction. The aims of the research are; 1) to analyze the construction of English verb “SEND” as a single verb; and 2) to analyze the Construction of English verb